DIGITAL TECHNOLOGY AND CHANGES IN CONSUMER BEHAVIOR : CASE STUDY OF THE MILLENNIAL GENERATION - Dewi Indriani Jusuf (Jurnal Ekonomi, 2023)
This research aims to investigate the impact of digital technology on consumer behavior, with a focus on the millennial generation. With rapid changes in digital technology, the millennial generation has become the group most affected by these changes in the context of consumer behavior. This research uses a qualitative approach involving in-depth interviews and content analysis to describe how digital technology has influenced consumer shopping habits, brand preferences and interactions. The research results show that the millennial generation has experienced significant changes in consumer behavior in response to advances in digital technology. They tend to prefer shopping online, respond positively to attractive digital marketing strategies, and are actively involved in brand-consumer interactions via social media. Additionally, changes in their consumption patterns are also reflected in a tendency to make impulse purchases and increased brand awareness, with a strong preference for products and services that offer an easy and engaging digital shopping experience.